2002
DOI: 10.1016/s0002-9440(10)64397-0
|View full text |Cite
|
Sign up to set email alerts
|

Different Pattern of Allelic Loss in Epstein-Barr Virus-Positive Gastric Cancer with Emphasis on the p53 Tumor Suppressor Pathway

Abstract: Both Helicobacter pylori (HP) and Epstein-Barr virus (EBV) have been implicated in carcinogenesis of the stomach. Fifty-seven gastric carcinomas were tested for microsatellite instability and allelic loss at several tumor suppressor loci using 21 polymorphic microsatellite markers. Furthermore, immunohistochemistry for p53 and DPC4/SMAD4 was performed. Results were analyzed according to HP and EBV status of the tumors, as assessed by immunohistochemistry and RNA in situ hybridization, respectively. Fractional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 24 publications
2
32
0
1
Order By: Relevance
“…The SMAD4 gene is located on chromosome region 18q21, and LOH in this region has been reported in 33% to 42% of gastric carcinomas (27,38). A summary of SMAD4 LOH and a comparison of chromosome 18q21 microsatellite markers are presented in Supplementary Table S5.…”
Section: Discussionmentioning
confidence: 99%
“…The SMAD4 gene is located on chromosome region 18q21, and LOH in this region has been reported in 33% to 42% of gastric carcinomas (27,38). A summary of SMAD4 LOH and a comparison of chromosome 18q21 microsatellite markers are presented in Supplementary Table S5.…”
Section: Discussionmentioning
confidence: 99%
“…have distinct molecular characteristics, as well as clinicopathological characteristics (5)(6)(7)(8). The loss of p16 protein is commonly associated with epigenetic mechanisms and is more common in EBV-infected tumors arising in the body of the stomach (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known regarding the molecular characteristics of EBV-positive gastric carcinomas. Recent studies suggest that hypermethylation of CpG islands is a mechanism of tumor suppressor gene silencing in EBV-positive gastric carcinomas (5), but allelic loss at some markers such as 5q [APC (adenomatous polyposis coli)], 17p (p53), and 18q (smad4) is inversely correlated with EBV positivity (6). The p53 tumor suppressor pathway (7) and microsatellite instability, a hallmark of a defective DNA mismatch-repair system (8), are not encountered in EBV-positive gastric carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous clinic paired comparative studies suggested that NM-3 had therapeutic effects on advanced gastric cancer. It could increase the surviving period of the patients, improve the life quality and increase the metastasis and recurrence after operation because of its lower toxic side-effect compared with intravenous chemical therapy [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] . Up to date, the effect of NM-3 on human gastric cancer has not been reported in the world.…”
Section: Discussionmentioning
confidence: 99%